Note—A Note on Jauch and Glueck, “Evaluation of University Professors' Research Performance” - Jauch, Lawrence R.; Ettlie, John (Management Science, 1976)
A Note on Jauch and Glueck, “Evaluation of University Professors' Research Performance” (Jauch, L. R., W. F. Glueck. 1976. Evaluation of university professors' research performance. Management Sci. 22 (1) 66–75.).